2010
DOI: 10.1088/0004-637x/724/2/1283
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Synthetic Spectra From Simulations of Relativistic Shocks

Abstract: Particle-in-cell (PIC) simulations of relativistic shocks are in principle capable of predicting the spectra of photons that are radiated incoherently by the accelerated particles. The most direct method evaluates the spectrum using the fields given by the Liénard-Wiechart potentials. However, for relativistic particles this procedure is computationally expensive. Here we present an alternative method, that uses the concept of the photon formation length. The algorithm is suitable for evaluating spectra both f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 29 publications
5
51
0
Order By: Relevance
“…In Keenan & Medvedev (2013), we found that the radiation spectrum, in the ultrarelativistic (small deflection angle) regime, agrees with the small-angle jitter radiation prediction (Medvedev 2000(Medvedev , 2006Reville & Kirk 2010;Medvedev et al 2011;Teraki & Takahara 2011). Furthermore, we demonstrated that the pitch-angle diffusion coefficient is directly related to, and can readily be deduced from, the spectra of the emitted radiation.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In Keenan & Medvedev (2013), we found that the radiation spectrum, in the ultrarelativistic (small deflection angle) regime, agrees with the small-angle jitter radiation prediction (Medvedev 2000(Medvedev , 2006Reville & Kirk 2010;Medvedev et al 2011;Teraki & Takahara 2011). Furthermore, we demonstrated that the pitch-angle diffusion coefficient is directly related to, and can readily be deduced from, the spectra of the emitted radiation.…”
Section: Introductionsupporting
confidence: 71%
“…It has been shown Medvedev (2006), Reville & Kirk (2010), Medvedev et al (2011) and Teraki & Takahara (2011) that mono-energetic ultrarelativistic electrons in this prescribed sub-Larmor-scale turbulence produce a flat angle-averaged spectrum below the spectral break and a power-law spectrum above the break, that is: 43) where the spectral break is ω j = γ 2 k min c, (2.44) which is called the jitter frequency. Similarly, the high-frequency break is…”
Section: Energy Diffusion In Small-scale Whistler Turbulencementioning
confidence: 99%
“…Moreover, even for an interaction with one SLSW, there are ambiguous points in the consideration of the typical frequency. To estimate the typical frequency of the radiation, we have to know the photon formation time (Akhiezer & Shul'ga 1987, Reville & Kirk 2010, which is the inverse of the cyclotron frequency mc/eB in the context of synchrotron radiation. Previous studies considered cases for which the phase-locking effect is weak, which means that the velocity is oblique to the wavevector direction.…”
Section: Introductionmentioning
confidence: 99%
“…An obvious candidate is the soft photon field produced by the interaction of thermal electrons with the Weibel-induced fluctuations -the 'jitter' analogue of the synchrotron photons produced by relativistic thermal electrons [10,3,12]. With these photons as targets, the radiation mechanism is analogous to the synchrotron self-Compton mechanism, which has been discussed in connection with the problem of rapidly decaying magnetic fluctuations [11,2].…”
Section: Discussionmentioning
confidence: 99%